(untitled) (Res Medica, 2013)
Based on an Address delivered to the Royal Medical Society, on Friday, 13th January. 1961. Just as the clinical picture of any pregnancy changes from week to week so the picture of obstetric practice as a whole is changing. As childbearing and childbirth have become safer for the mother more and more attention has been directed to her unborn child. The foetus and its placenta, however are remote when compared with the mother and therefore can often only be studied indirectly.